Pengaruh Kecerdasan Emosional dan Kompetensi terhadap Kinerja Pegawai pada Dinas Perindustrian dan Tenaga Kerja Kabupaten Badung - Ni Kadek Setiari; Ni Luh Sili Antari; Luh Gede Putri Kusuma Pekerti (Universitas Triatma Mulya, 2024)
Employee performance is one thing that needs to be considered in a company or agency, because employee performance certainly has an impact on employee performance in achieving goals. The problem raised in this study is whether emotional intelligence (X1) affects employee performance (Y) at the Badung Regency Industry and Labor Office, does competence (X2) affect employee performance (Y) at the Badung Regency Industry and Manpower Service , what is the influence of emotional intelligence and competence on employee performance at the Badung Regency Industry and Manpower Service and which independent variables have a dominant influence on employee performance at the Badung Regency Industry and Manpower Service. The population in this study amounted to 56 people. This study uses the population as a sample. The data analysis technique used is descriptive analysis, data quality test, classical assumption test, multiple linear regression analysis, t-test analysis, determination analysis, and beta coefficient. The results of the analysis show that emotional intelligence (X1) has a partial positive and significant effect on employee performance (Y) at the Office of Industry and Labor in Badung Regency. Competence (X2) partially has a positive and significant effect on employee performance (Y) at the Badung District Office of Industry and Labor. The magnitude of the influence of emotional intelligence and competence on employee performance at the Badung District Office of Industry and Labor is 52.1% and the remaining 47.9% is influenced by other variables not examined in this study. The independent variable that has a dominant influence on employee performance can be seen in the value of Standardized Coefficients Beta, which is the variable emotional intelligence (X1).